Rumah Pintar Pemilihan Umum Komisi Pemilihan Umum Kota Semarang Sebagai Pusat Pembelajaran Pemilih - Henry Wahyono; Laila Kholid Alfirdaus (Mahesa Research Center, 2021)
Smart House for general election is a means of political education from the Electoral Commission that provides information about elections from time to time. Hopefully there will be many voters who want to know about the Election through the Smart Home Elections. The purpose of the study was to analyze the role of the Semarang KPU Election Smart House as an election learning center for voters. This research uses descriptive qualitative methods, as well as data collection through in-depth interviews and direct obeservation. The informant of this research consists of the Secretariat and Commissioners, as well as visitors to the Kpu Election Smart House in Semarang City. Technical data analysis refers to miles and huberman models include, data reduction, data display and draw conclusions. The results showed that The Smart House of Kpu Semarang City elections conducts political education activities through audio visual rooms, showrooms, discussion rooms and simulation rooms. In addition, political education is carried out with radio, leaflets, web and social media such as Facebook, Twitter, Instagram and Youtube. Furthermore, make visits to schools and cooperate with universities. There are many obstacles faced in conducting political education influenced by inadequate human resources and limited budget.